2018
DOI: 10.1002/celc.201800213
|View full text |Cite
|
Sign up to set email alerts
|

In situ Synthesis of V2O3‐Intercalated N‐doped Graphene Nanobelts from VOx‐Amine Hybrid as High‐Performance Anode Material for Alkali‐Ion Batteries

Abstract: V2O3 is a promising anode material for lithium‐ and sodium‐ion batteries due to its high theoretical capacity and natural abundance. However, the low conductivity, sluggish ion reaction kinetics, and large volume change limit the rate and cycling stability in batteries. In this work, the V2O3‐nanoparticles‐intercalated N‐doped graphene (V2O3/NG) hybrid is prepared by one‐step controlled pyrolysis of inorganic‐organic hybrid VOx/3‐phenylpropylamine nanobelts under Ar. The intercalated 3‐phenylpropylamine molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Two types of vanadium oxides (V 2 O 3 and V 2 O 5 ) are investigated for LIB and SIB applications; the former is treated as of conversion‐type, and its capacity in SIB systems is much smaller than in LIBs due to the negative voltage shift of 0.96 V between the two systems. [ 229,230 ] V 2 O 5 , on the contrary, was usually used as a cathode material based on intercalation mechanisms, thought the conversion reaction 0.1V 2 O 5 + Na → 0.5Na 2 O + 0.2V is thermodynamically possible (reaction enthalpy: −0.57 eV). [ 231,232 ] Above 1.2 V vs Na + /Na, V 2 O 5 would turn into mixture of NaV 2 O 5 and Na 2 V 2 O 5 upon sodium insertion, with the specific capacity less than 295 mAh g −1 (the theoretical value based on Na 2 V 2 O 5 ), and the crystalline structure could be recovered upon the sodium extraction.…”
Section: Intercalation‐type Materialsmentioning
confidence: 99%
“…Two types of vanadium oxides (V 2 O 3 and V 2 O 5 ) are investigated for LIB and SIB applications; the former is treated as of conversion‐type, and its capacity in SIB systems is much smaller than in LIBs due to the negative voltage shift of 0.96 V between the two systems. [ 229,230 ] V 2 O 5 , on the contrary, was usually used as a cathode material based on intercalation mechanisms, thought the conversion reaction 0.1V 2 O 5 + Na → 0.5Na 2 O + 0.2V is thermodynamically possible (reaction enthalpy: −0.57 eV). [ 231,232 ] Above 1.2 V vs Na + /Na, V 2 O 5 would turn into mixture of NaV 2 O 5 and Na 2 V 2 O 5 upon sodium insertion, with the specific capacity less than 295 mAh g −1 (the theoretical value based on Na 2 V 2 O 5 ), and the crystalline structure could be recovered upon the sodium extraction.…”
Section: Intercalation‐type Materialsmentioning
confidence: 99%
“…Recently, transition metal oxides have been regarded as advanced alternatives owing to their higher theoretical capacity (>700 mA h g −1 ), natural abundance and low cost, such as Fe 2 O 3 , Co 3 O 4 , MnO, etc. Among these anode material candidates, V 2 O 3 has become a promising anode material for LIBs owing to the merits of higher specific capacity (1070 mA h g −1 ), multi‐oxidation states and low toxicity ,. However, dramatic volume variation during lithiation and delithiation process and low electrical conductivity prohibit its practical utilization in LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we found that the property of the CV-600 electrode is much better than some V 2 O 3 /C composites reported in the open literature 17,39,36,37,40,41 as shown in Table S1. Obviously, the most important distinctiveness of the CV-600 composite has a unique peapod-like structure.…”
Section: ■ Results and Discussionmentioning
confidence: 69%